A highly stable bio-based plasticizer constructed from renewable acids for plasticizing and enhancing the optical properties of poly(vinyl chloride). (22nd December 2022) - Lu, Minjia; Jiang, Pingping; Zhang, Pingbo; Feng, Shan; Cui, Zhixuan; Song, Qingkui; Zhao, Yong
Abstract : The current research efforts in the plasticizer industry should focus on finding renewable biomass chemical feedstocks to synthesize non-toxic and effective bio-based plasticizers to adapt the concept of green environmental protection. Abstract : The current research efforts in the plasticizer industry should focus on finding renewable biomass chemical feedstocks to synthesize non-toxic and effective bio-based plasticizers in order to adapt to the concept of green environmental protection given the scarcity of petroleum resources and the growing emphasis on health and environmental protection. In this study, lactic acid, dl -malic acid, and levulinic acid were used as the main raw materials in a three-step esterification reaction to successfully synthesize a novel high-efficiency plasticizer (LLMEE) containing multiple ester groups. The structure of LLMEE was characterized and confirmed by FT-IR, 1 H NMR, and time of flight mass spectrometry (TOF-MS). The plasticizing properties of LLMEE in PVC were tested and compared to the commercial plasticizers acetyl tributyl citrate (ATBC) and dioctyl phthalate (DOP). The results of optical performance showed that, compared to ATBC and DOP, PVC plasticized by 50 phr LLMEE had both high transparency and UV resistance. According to the results of tensile tests, the elongation at break of PVC plasticized by 60 phr LLMEE reached 833.1%, indicating its excellent mechanical properties. The TGA results showed that the thermal stability of PVC plasticized by LLMEE was comparable to that of PVC plasticized by DOP or ATBC. Most importantly, LLMEE exhibited excellent migration stability in various leaching tests compared to commercial plasticizers. Taken together, the results indicated that compared with ATBC and DOP, LLMEE had better comprehensive performance, and provides a new choice to rationally utilize biomass raw materials to prepare novel environmentally friendly plasticizers.